Microbe Profile: Xylella fastidiosa – a devastating agricultural pathogen with an endophytic lifestyle. Issue 10 (1st October 2021) - Burbank, Lindsey P.; Roper, M. Caroline
Abstract : Xylella fastidiosa is a vector-borne plant vascular pathogen that has caused devastating disease outbreaks in diverse agricultural crops worldwide. A major global quarantine pathogen, X. fastidiosa can infect hundreds of plant species and can be transmitted by many different xylem sap-feeding insects. Several decades of research have revealed a complex lifestyle dependent on adaptation to the xylem and insect environments and interactions with host plant tissues.